Effectiveness Of Political Party Financial Assistance Program On Political Education For Political Party Cadres In Riau Islands Province - Ikhsan Yuditra Usman; Edy Akhyary; Fitri Kurnianingsih (Kemudi, 2025)
The phenomenon of this research is to see the financial assistance channeled to political parties, especially in the Riau Islands Province towards the implementation of Political Education for their respective Political Party Cadres. According to the Indonesian Democracy Index (IDI), in 2022-2023 Riau Islands Province in the 22nd indicator, namely "Political Education for Political Party Cadres" has decreased, with a score of 40.00 in 2022 and 22.00 in 2023. Thus, the purpose of this study is to identify whether the effectiveness of financial assistance provided to political parties has a significant impact or not. The theory used in this research is according to Richard M. Steers in Sutrisno (2007), which has 3 indicators in programme effectiveness, namely Task Achievement, Integration, and Adaptation. The method in this research uses descriptive qualitative research, with data analysis techniques in the form of data reduction, data presentation, and conclusion drawing. The results of this study indicate Task Achievement, financial assistance provided by the Riau Islands Provincial Government to political parties will be funded after BPK RI approves the funding provided. Integration, Kesbangpol Riau Islands Province as a channel in receiving proposals and accountability reports for political parties, has conducted socialisation related to examples and uses of financial assistance received by political parties. And, Adaptation, Kesbangpol has collaborated with various related parties in verifying the results of the accountability reports provided by political parties. The conclusion in this study is that the political education provided by political parties, namely PDI Perjuangan, PKS, Democrat, Golkar, and PPP, states that they have carried it out properly and have been reported through accountability reports to Kesbangpol.